Cluster approach to sustainable tourism development: Pendekatan kluster untuk pengembangan pariwisata berkelanjutan - Ravshan Allayorov (Universitas Muhammadiyah Sidoarjo, 2019)
The article considers the cluster approach to the sustainable development of tourism destinations. The concept of the